2013
DOI: 10.3390/ijms140714426
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Thyroid-Stimulating Hormone Receptor on Nano-Sized Bacterial Magnetic Particles in Magnetospirillum magneticum AMB-1

Abstract: The measurement of autoantibodies to thyroid-stimulating hormone receptor (TSHR) is important for the diagnosis of autoimmune thyroid disease such as Graves’ disease (GD). Although TSHR from porcine thyroid membrane is commonly used for the measurement of TSHR autoantibodies (TRAb), recombinant human TSHR (hTSHR) remains ideal in terms of stable supply and species identity. Here we set out to express recombinant hTSHR on the lipid-bilayer surface of magnetic nanoparticles from a magnetotactic bacterium, Magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The amount of Mms13-TrkA fusion protein on the magnetosomes was calculated as 106 ng/mg of magnetosomes based on the calibration curve. This value was comparable to that of the thyroid-stimulating hormone receptor and Mms13 fusion protein (17.2 ng/mg of magnetosome) that has been used for autoantibody detection (19). These results indicate that a sufficient amount of TrkA on magnetosomes was successfully produced for the ligand-binding assay.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The amount of Mms13-TrkA fusion protein on the magnetosomes was calculated as 106 ng/mg of magnetosomes based on the calibration curve. This value was comparable to that of the thyroid-stimulating hormone receptor and Mms13 fusion protein (17.2 ng/mg of magnetosome) that has been used for autoantibody detection (19). These results indicate that a sufficient amount of TrkA on magnetosomes was successfully produced for the ligand-binding assay.…”
Section: Resultssupporting
confidence: 61%
“…Target proteins can be efficiently expressed on magnetosomes using Mms13 as a fusion partner (16). The system for target protein expression on magnetosomes using Mms13, which we call the magnetosome display system, has enabled us to produce a wide range of functional proteins, such as an estrogen receptor, a D1 dopamine receptor, and a thyroid-stimulating hormone receptor (17)(18)(19). These receptors are major targets for drug discovery, some of which were not successfully expressed in E. coli because of cytotoxic effects.…”
mentioning
confidence: 99%
“…Interestingly, magnetosomes can be functionalized in vivo by fusing foreign proteins of interest to the magnetosome membrane proteins, such as MamC/Mms13, MagA, and Mms16 (Arakaki et al, 2008;Ren et al, 2018). The translational fusion of functional proteins to these transmembrane proteins of magnetosomes has led to numerous successful prototypes in a wide range of applications, including of industrial uses (Ginet et al, 2011;Sugamata et al, 2013;Honda et al, 2015a,b;Xiang et al, 2017;Mickoleit and Schüler, 2018). The inherent magnetic characteristics of magnetosomes make them very useful in some situations, especially for implementation in magneticfield-related technologies, such as magneto-immunoassays and biomedical imaging (Ren et al, 2018).…”
Section: Magnetosomesmentioning
confidence: 99%
“…Sugamata (2013) expressed recombinant hTSHR on the lipid-bilayer surface of magnetosomes using a tetracyclineinducible expression system. Further, it was suggested that hTSHR-displayed magnetosomes had potential for ligandreceptor interaction analysis in GD patients.…”
Section: Detection System/in Immunoassaymentioning
confidence: 99%